(untitled) (Jurnal Peternakan Lingkungan Tropis, 2024)
Red ginger is also known as (Zingiber offinale Var. Rubrum), is a plant that functions as a natural preservative for meat and has bioactive compounds that can improve meat quality by inhibiting microbial growth. The purpose of this study was to determine how the total bacteria of broiler chickens are affected by red ginger decoction. Completely Randomized Design (CRD) was used with 4 treatments, namely P0 (control), P1 (soaking in red ginger decoction for 30 minutes), P2 (soaking in red ginger decoction for 60 minutes), and P3 (soaking in red ginger decoction for 90 minutes). This study used the TPC (Total Plate Count) test. This study used ANOVA, Duncan and Orthogonal Polynomial for data analysis. The addition of red ginger decoction affects the total bacteria in broiler chicken meat.